PEMANENAN AIR HUJAN SEBAGAI ALTERNATIF SUMBER AIR BERSIH UNTUK KEBUTUHAN MASYARAKAT DESA MESIAPI KABUPATEN MALUKU BARAT DAYA - Nirahua, Efata; Betaubun, Renny James; Titaley, Henriette Dorothy (Journal Agregate, 2024)
Rainwater is harvested through a simple system commonly called Rain Water Harvesting. The purpose of this research is to determine the quality of rainwater to be harvested, the potential discharge that can be utilized, and the design of the PAH system for Mesiapi Village, Southwest Maluku Regency. The method of determining the quality of rainwater is done by collecting rainwater and then testing it in the laboratory. Analysis of rainfall frequency using continuous probability, namely the distribution of gumbel and log person III then tested the probability distribution using the Chi square test, to determine the discharge of clean water that can be harvested, after that planning the design and cost budget for making a recervoir tub. The results of water quality testing show a pH value of 8.11; Temperature 24.4°C; and TDS 22.9 mg/l. The highest rainfall value in Mesiapi village for 10 years with the highest rainfall level occurred in 2020, namely 260 mm. The rainfall return period is 2 years with a rain duration of 2 hours, with the Log Person III distribution obtaining a rainfall plan value of 7.857 mm/hour and a discharge of 61 lt/det. The draft cost budget obtained from the calculation for the construction of a recervoir (reservoir) in Mesiapi village with a plan for 2 reservoirs is IDR 665,284,000.